Instagram Marketing Strategy Improvement Design of Vrans Studio Detailing Using Benchmarking and Analytic Hierarchy Process Methods - Wali Hakim Pradana; Agus Achmad Suhendra; Ima Normalia Kusmayanti (Jurnal Mirai Management, 2022)
Vrans Studio Bandung (VSD) is one of the automotive detailing companies in Bandung which started in 2017. Initially 2017, the business focused on detailing the car with only a few customers per day. Now, apart from detailing, VSD also offers washing, repainting, repairing, and coating for parts and whole of cars, motorcycles, and bicycles. Currently, the VSD business can wash 70 vehicles per month. Seeing the sale, the owner aims to expand the market, especially the Bandung city area. However, in meeting its objectives, the owner has constraints, namely limited costs, labor, and marketing which is currently done only by marketing products on Instagram, conducting sales promotions, word of mouth and the use of WhatsApp. With these obstacles, VSD business owners cannot achieve their goals. Therefore, this Final Project uses the benchmarking method through checklist observations to identify gaps and find best practices from competitors' performance in Instagram marketing communications. Keywords: Marketing Communications, Instagram dan VSD